STRATEGI JEPANG MENGEMBANGKAN WORLD HALAL TOURISM MENARIK WISATAWAN MUSLIM INDONESIA KE JEPANG - Holly Dwi Futrianota; Syafri Harto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The increase of moeslem tourist sum triggers the growing halal tourism business in Japan. Japan is succeeding to reach the award as “World Best Non OIC Emerging Halal Destination” in World Halal Tourism Award 2016 that was implemented in Abu Dhabi, UEA. The moeslem tourist of Indonesian is interested to visit Japan because of two things, namely, first, internal factor, the service and the preparation of infrastructure are built and prepared for the moeslem people. The second, external factor.The middle society of Indonesian moeslem from the economy site with travelling hobby. Theory are used in this research is city branding theory of Terrence Schimp. The method used in this research is descriptive qualitative. The data were collected through observations and documentations. The technique of data analysis which used in this research was qualitative method and descriptive approachment. Japan makes effort to develop world halal tourism in interest Indonesian moeslem tourist through the concept of halal supply chain management. This concept is implemented by cooperating with the influencer that has so many follower such as the blogger travel from Indonesian. Next, Increasing the facility and the service based on the concept of moslem friendly and putting into effect the visa free for the the tourist of Indonesian, Malaysia and Thailand. Furthermore, Japan determines the halal certification, standard operational and halal requirement. Keywords: Halal Tourism, Supply Chain Management, Moeslem Tourist